2001
DOI: 10.1002/bit.1159
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐particle oxygen diffusion limitation in solid‐state fermentation

Abstract: Oxygen limitation in solid-state fermentation (SSF) has been the topic of modeling studies, but thus far, there has been no experimental elucidation on oxygen-transfer limitation at the particle level. Therefore, intra-particle oxygen transfer was experimentally studied in cultures of Rhizopus oligosporus grown on the surface of solid, nutritionally defined, glucose and starch media. The fungal mat consisted of two layers--an upper layer with sparse aerial hyphae and gas-filled interstitial pores, and a dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
15

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 42 publications
(40 reference statements)
2
32
0
15
Order By: Relevance
“…A total number of 10 5 conidia were point inoculated on AMM-Agar with 10 % (v/v) Gyamerah 1995;Wang et al 2005). Also, in solid-state fermentations of the zygomycete Rhizopus oligosporus, microelectrode measurements have shown that in mature fungal mats, O 2 saturation is only maintained at the colony surface and decreases rapidly to nearly anaerobic levels within less than a few hundred micrometers distance (Oostra et al 2001). This O 2 gradient is exploited by the formation of the aerial hyphae, which function as the fungal respiratory organs, accomplishing around 75 % of the mycelial O 2 uptake in A. oryzae (Rahardjo et al 2002).…”
Section: Oxygen Levels In the Field Lab And Hostmentioning
confidence: 99%
“…A total number of 10 5 conidia were point inoculated on AMM-Agar with 10 % (v/v) Gyamerah 1995;Wang et al 2005). Also, in solid-state fermentations of the zygomycete Rhizopus oligosporus, microelectrode measurements have shown that in mature fungal mats, O 2 saturation is only maintained at the colony surface and decreases rapidly to nearly anaerobic levels within less than a few hundred micrometers distance (Oostra et al 2001). This O 2 gradient is exploited by the formation of the aerial hyphae, which function as the fungal respiratory organs, accomplishing around 75 % of the mycelial O 2 uptake in A. oryzae (Rahardjo et al 2002).…”
Section: Oxygen Levels In the Field Lab And Hostmentioning
confidence: 99%
“…As the fungal mycelium develops on a solid surface, the void spaces between the hyphae can either be fully or partially filled with water. In the former case, it results in severe oxygen limitation causing anaerobic conditions affecting the performance of SSF [27,28]. The phytase production was 10.59% higher with forced air (1.0 N mL g -1 min -1 and 65% of initial moisture), achieving the average of 94.24 U gds -1 [more than without forced air (84.26 U gds -1 )].…”
Section: Resultsmentioning
confidence: 94%
“…In SSF, the operating conditions like temperature, pH and moisture content are vital factors influencing the microbial growth and production of cellulase. Availability of oxygen in the open space between substrate particles (i.e., porosity) and generation of heat are the major challenges in SSF, which have to be addressed properly [55,56].…”
Section: Solid-state Fermentationmentioning
confidence: 99%